Effect of silymarin supplementation on some productive and hematological parameters in meat type male Japanese quails - Ivelina Pavlova, Hristo Lukanov; Yoana Petrova, Nadya Bozakova, Veselin Ivanov, Todor Slavov (Emirates Journal of Food and Agriculture, 2019)
A total of 90 14-day-old meat type male Japanese quails were included in the experiment and equally divided into 3 groups: control group (CG) without treatment, experimental group 1 (EG 0.5%), supplemented with silymarin 0.5% and experimental group 2 (EG 1%), supplemented with silymarin 1%. The aim of the current study was to establish the effect of supplementation with different doses of silymarin extract on the growth performance and some hematological parameters in male Japanese quails. Main growth performance (body weight, feed consumption and weight gain) were examined and FCR was calculated. Some hematological (WBC, RBC, HGB and HTC) and biochemical (triglycerides, AST and ALT) parameters were determined. The highest average body weight was observed in EG 0.5% group at 35-day-old age and the lowest in EG 1%, 239.61±2.96 g and 231.74±2.96 g respectively. The highest values of the weight gain were calculated in EG 0.5% group, 67.02±2.03 g during the first week of fattening and the lowest was observed in EG 1% group at the fifth week after hatching, 23.30±2.03 g respectively. The lowest values of FCR were observed during the first week of the trial, 2.42±0.08 kg/kg to 2.61±0.13 kg/kg in EG 1% and the control group respectively. The supplementation of 0.5% and 1% silymarin did not significantly change the studied hematological and biochemical parameters. A tendency of higher values of triglycerides and lower values of AST and ALT was observed in the groups, supplemented with silymarin compared to the controls. From the obtained results of the present study we can conclude that the silymarin supplementation at higher doses (0.5% and 1%) did not have effect on the main growth performance and some hematological and biochemical parameters of male Japanese quails.